[tex]\bf n^{th}\textit{ term of an arithmetic sequence}\\\\
a_n=a_1+(n-1)d\qquad
\begin{cases}
n=n^{th}\ term\\
a_1=\textit{first term's value}\\
d=\textit{common difference}
\end{cases}\\\\
-------------------------------\\\\[/tex]
[tex]\bf A(n)=12+(n-1)(3)\qquad \begin{cases}
n=n^{th}\ term\\
12=\textit{first term's value}\\
3=\textit{common difference}
\end{cases}
\\\\\\
n=1,4\ and\ 10\implies
\begin{cases}
A(\underline{1})=12+(\underline{1}-1)(3)\\
A(\underline{4})=12+(\underline{4}-1)(3)\\
A(\underline{10})=12+(\underline{10}-1)(3)
\end{cases}[/tex]